Variability in a three‐generation family with pierre robin sequence, acampomelic campomelic dysplasia, and intellectual disability due to a novel ∼1 Mb deletion upstream of SOX9, and including KCNJ2 and KCNJ16. Issue 1 (11th December 2015) - Castori, Marco; Bottillo, Irene; Morlino, Silvia; Barone, Chiara; Cascone, Piero; ,; Grammatico, Paola; Laino, Luigi
Abstract : Background: Campomelic dysplasia and acampomelic campomelic dysplasia (ACD) are allelic disorders due to heterozygous mutations in or around SOX9 . Translocations and deletions involving the SOX9 5′ regulatory region are rare causes of these disorders, as well as Pierre Robin sequence (PRS) and 46, XY gonadal dysgenesis. Genotype–phenotype correlations are not straightforward due to the complex epigenetic regulation of SOX9 expression during development. Methods: We report a three‐generation pedigree with a novel ∼1 Mb deletion upstream of SOX9 and including KCNJ2 and KCNJ16, and ascertained for dominant transmission of PRS. Results: Further characterization of the family identified subtle appendicular anomalies and a variable constellation of axial skeletal features evocative of ACD in several members. Affected males showed learning disability. Conclusion: The identified deletion was smaller than all other chromosome rearrangements associated with ACD. Comparison with other reported translocations and deletions involving this region allowed further refining of genotype–phenotype correlations and an update of the smallest regions of overlap associated with the different phenotypes. Intrafamilial variability in this pedigree suggests a phenotypic continuity between ACD and PRS in patients carrying mutations in the SOX9 5′ regulatory region. Birth Defects Research (Part A) 106:61–68, 2016 . © 2015 Wiley Periodicals, Inc.